2019
DOI: 10.3390/ijms20153636
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Overexpressed OsCIPK2 Rice as a Nitrogen Utilization Efficient Crop and Analysis of Its Associated Rhizo-Compartmental Microbial Communities

Abstract: Nitrogen (N) is one of the indispensable factors in rice growth and development. China holds a premier position in the production of rice and at the same time also faces higher N fertilizer costs along with serious damage to the environment. A better solution is much needed to address these issues, without disrupting the production of rice as an important cereal, while minimizing all the deleterious effects on the environment. Two isogenic lines Kitaake (WT) and its genetically modified line CIPK2 (RC), overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…It has been documented that B. aphidicola, an aphid endosymbiont, influences herbivore behaviors by modulating plant volatile profiles, implying that CMV infections reduce the abundance of B. aphidicola in aphids, which has been associated with a preference shift in aphids from infected to healthy plants (Shi et al, 2021). It is revealed that the symbiotic bacteria affect feeding tropisms and feeding behaviors of insects and influences plant infections by viruses (Frago et al, 2012;Simon et al, 2017;Khan et al, 2019;Noman et al, 2020).…”
Section: Bacterial Symbionts Influence Plant Virus Infectionsmentioning
confidence: 99%
“…It has been documented that B. aphidicola, an aphid endosymbiont, influences herbivore behaviors by modulating plant volatile profiles, implying that CMV infections reduce the abundance of B. aphidicola in aphids, which has been associated with a preference shift in aphids from infected to healthy plants (Shi et al, 2021). It is revealed that the symbiotic bacteria affect feeding tropisms and feeding behaviors of insects and influences plant infections by viruses (Frago et al, 2012;Simon et al, 2017;Khan et al, 2019;Noman et al, 2020).…”
Section: Bacterial Symbionts Influence Plant Virus Infectionsmentioning
confidence: 99%
“…Previous research indicated that receptor-like protein kinases (RLKs) are involved in signal transduction pathways associated with abiotic stress stimuli in plants [ 50 ]. Besides, overexpression of the genes encoding CBL-interacting protein kinase (CIPK) enables rice to exhibit a higher NO 3 − uptake capacity under low-N stress [ 51 ]. In the present study, different groups of PK genes were identified, which mainly included MAPK, RLK, and CIPK families ( Table S4 ).…”
Section: Discussionmentioning
confidence: 99%
“…A calciumdependent protein kinase gene, esl4, which may function upstream of N-metabolism genes [55]. The overexpression of Calcineurin B-like interacting protein kinase 2 gene, OsCIPK2, could increase N use efficiency in rice [56]. OsSAPK8 is a counterpart of AtOST1 in the activation of OsSLAC1, which is a nitrate-selective anion channel in rice [57].…”
Section: Discussionmentioning
confidence: 99%